Sustainability Consciousness Integration into Healthcare Service Delivery in Gombe State, Nigeria - Ishaku Yusuf Aliyu; Wadai Darama Mallum; Bula Benjamin Yunah; Nathaniel Richard; Bitrus Jibrin; Prof. Magaji Abba (Journal of Current Research and Studies, 2026)
Sustainable healthcare is becoming an increasingly prominent issue as the aspects and impacts of healthcare activities are acknowledged and discovered. The study aimed at assessing the sustainability consciousness integration into healthcare service delivery in Gombe State, Nigeria, through identifying macro-area’s criteria that institute sustainability consciousness in healthcare sector in Gombe State, evaluating the path to sustainability consciousness for healthcare service demand and supply in Gombe State, and assessing the relationship of macro-area’s criteria and the path to sustainability consciousness for healthcare demand and supply in healthcare sector in Gombe State. The study adopted a cross-sectional field survey research design with 90 professional health personnel as the sample size of the study administered with a validated and reliable (α = 0.70) questionnaire instrument for collecting the primary data of the study. Both descriptive and inferential statistics were used in analysing the study objectives with the used of SPSS version 23 software as a tool for data analyses. The study concluded that, environmental macro-area criteria with envelope technologies and social macro-area criteria with comfort are the highest important macro-area’s criteria that institute sustainability consciousness in healthcare sector in Gombe State. Foster skill to create value-conscious consumers, promoting technology innovations that lower cost and leverage talent to raise quality, and implementing modern management and focus on performance are the three most path to sustainability consciousness for healthcare demand and supply in Gombe State. There was large positive significant relationship between the macro-area’s criteria that institute sustainability consciousness and the paths to sustainability consciousness for healthcare demand and supply in healthcare sector in Gombe State (N=78, r=0.631, p<0.05). The study recommended that, stakeholders and medical professionals need to create a serious awareness to the entire public for the paramount importance to shift utmost attention to integrate sustainability consciousness in their dealings in healthcare sector, and more needs to be invest in healthcare sector so to increase clinical and technological performances in the sector. more statutory laws should be worked and put in place both locally, nationally, and globally to ensure more paths to sustainability consciousness for healthcare service demand and supply to achieve high quality of healthcare for all. Government and relevant stakeholders should buckle up and embark on a holistic approach with no sentiment that will encourage sanity in the healthcare sector and guarantee safety for all habitat which can ensure sustainability consciousness in healthcare.